Water Rescue Training for KSR Members of PMI Serdang Bedagai Regency - Syahferi Anwar; Damanik, Balqis Nurmauli (Indra Institute Research & Publication, 2024)
The Water Rescue Training for KSR Members of PMI Serdang Bedagai Regency is a strategic initiative designed to enhance the preparedness and operational capabilities of student volunteer teams in responding to water-related emergencies. This training program integrates both theoretical instruction and practical simulations to equip participants with essential skills in water rescue techniques, emergency medical responses, and the operation of rescue equipment such as rubber boats. Given the frequent occurrence of floods and other water-related disasters in Indonesia, the training emphasizes rapid and effective response strategies to minimize casualties and property damage. The program also focuses on improving team coordination and communication, which are critical for managing complex rescue scenarios. By covering a wide range of potential water rescue situations, the training ensures that KSR members are adaptable and capable of addressing various emergencies. Continuous learning and skill refinement are integral components of the program, ensuring that participants remain proficient in the latest rescue techniques. Overall, this training significantly contributes to the readiness and effectiveness of PMI Serdang Bedagai Regency's volunteer teams, enhancing community safety and resilience against water-related disasters.